Zones of conflict in Africa theories and cases - Kieh, George Klay 1956-; Mukenge, Ida Rousseau 1941- (Praeger, 2002)
Torn by ongoing civil and military violence, Africa presents a challenge to scholars interested in the root causes of conflict. Each conflict is unique, but overall they exhibit common patterns. The contributors of this book employ an eclectic array of current explanations of civil strife and how to resolve it. The first half of the book provides the relevant theoretical background. Theories of conflict and conflict resolution, the larger context of African strife in Africa, and patterns and trends of conflict are discussed. Shifting from the general to the particular, the remaining chapters of this volume gauge the accuracy and usefulness of the current thinking on conflicts by grounding it in case studies drawn from the Great Lakes Region, Liberia, Nigeria, and Zambia.